Cambridge primary English learner's book 2 - Budgell, Gill (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Learner's Book 2 is part of a series designed to help young learners build essential English language skills. It focuses on developing reading, writing, listening, and speaking abilities through engaging activities, stories, and exercises. The book introduces key grammar concepts, vocabulary, and sentence structures in a way that is accessible and enjoyable for primary school students. It aims to foster both language proficiency and a love for learning, with clear explanations and supportive practice exercises throughout the book.
Keywords: English : Textbook